THE LOCAL PRODUCTION OF LAMPS IN ALBURNUS MAIOR: WORKSHOPS OR LOCAL BRANCHES? - Bocan, Ionuț; Neagu, Cătălina-Mihaela (Rei Cretariae Romanae Fautorum Acta, 2022)
Alburnus Maior (nowadays Roșia Montană, Alba County, Romania) is situated in the area of the region known as 'Golden Quadrilateral' of the Western Carpathians. Although the archaeological research carried out in Alburnus Maior did not reveal defining elements of the lamps production: clay extraction, pottery kilns, archetypes or moulds, a series of indications can provide important arguments regarding the existence of workshops that produced lamps. Thus, the possibilities to identify local workshops that produced lamps are limited, being reduced to the analysis of their finished products. An important collection of lamps consisting of 1694 items was examined for this study. It should be mentioned the fact that the majority of the lamps were found in a funerary context.